2010
DOI: 10.3402/gha.v3i0.2126
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health and well-being among older people in rural South Africa

Abstract: BackgroundThe population in developing countries is ageing, which is likely to increase the burden of non-communicable diseases and disability.ObjectiveTo describe factors associated with self-reported health, disability and quality of life (QoL) of older people in the rural northeast of South Africa.DesignCross-sectional survey of 6,206 individuals aged 50 and over. We used multivariate analysis to examine relationships between demographic variables and measures of self-reported health (Health Status), functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 22 publications
12
80
0
Order By: Relevance
“…In addition, diabetes status per se was associated with poor quality of life and disability, as were socio-economic status (low education), being in a low wealth quintile, having a poor employment history, marital status (not being in a partnership), lifestyle habits (low physical activity, history of alcohol use) and co-morbid conditions. In accordance with previous studies, we found that having  diabetes [2022], having lower formal education levels [23–25], being in a low socioeconomic group [26,27], not being in a marital relationship [28,29] and not having worked [30,31] were significantly associated with poor quality of life and a high level of disability, but unlike findings in other studies [3235], being older and being female were not associated with a high level of disability 20222325 26,27 28,29]30,31 3235 The differences in findings in this study compared to others may relate to the use of different instruments to assess the quality of life and disability, as well as the use of diabetes-specific and generic measures across studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, diabetes status per se was associated with poor quality of life and disability, as were socio-economic status (low education), being in a low wealth quintile, having a poor employment history, marital status (not being in a partnership), lifestyle habits (low physical activity, history of alcohol use) and co-morbid conditions. In accordance with previous studies, we found that having  diabetes [2022], having lower formal education levels [23–25], being in a low socioeconomic group [26,27], not being in a marital relationship [28,29] and not having worked [30,31] were significantly associated with poor quality of life and a high level of disability, but unlike findings in other studies [3235], being older and being female were not associated with a high level of disability 20222325 26,27 28,29]30,31 3235 The differences in findings in this study compared to others may relate to the use of different instruments to assess the quality of life and disability, as well as the use of diabetes-specific and generic measures across studies.…”
Section: Discussionsupporting
confidence: 92%
“…According to Townsend and Wilcock 5 , occupational imbalance is experienced by people who are un-occupied, under-occupied or over-occupied. Regarding the literature that deals with the challenges faced by family caregivers, it could be argued that they experience challenges in balancing their occupational demands related to their caregiver role, family, and career 15 . Previous studies reported that family caregivers seemed to experience caregiver burden, as they spent most of their time providing (or helping with) the self-care activi-ties of the older adults 5,16 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] (ii) Health and functional impairments may significantly impact on older persons' quality of life. 41,42 (iii) Within the older population, levels of ill-health and impaired function clearly vary between sociodemographic (e.g., gender, rural/urban, socioeconomic) groups.…”
Section: Policy Challengesmentioning
confidence: 99%
“…41,42 (iii) Within the older population, levels of ill-health and impaired function clearly vary between sociodemographic (e.g., gender, rural/urban, socioeconomic) groups. 28,29,34,[37][38][39][40] Evidence suggests a consistently higher risk of disability, depression, dementia as well as self-reported poor health and function among older women compared to men. Findings on relationships of rural/urban and socioeconomic status to health outcomes, however, are less clear.…”
Section: Policy Challengesmentioning
confidence: 99%